Prostanoids for critical limb ischaemia - Ruffolo, Antonio J. (2010)
Background Peripheral arterial occlusive disease (PAOD) is a common cause of morbidity and mortality due to cardiovascular disease in the general population. Although numerous treatments have been adopted for patients at different disease stages, no option other than amputation is available for patients presenting with critical limb ischaemia (CLI) unsuitable for rescue or reconstructive intervention. In this regard, prostanoids have been proposed as a therapeutic alternative, with the aim of increasing blood supply to the limb with occluded arteries through their vasodilatory, antithrombotic, and anti-inflammatory effects. This is an update of a review first published in 2010. Objectives To determine the effectiveness and safety of prostanoids in patients with CLI unsuitable for rescue or reconstructive intervention. Search methods For this update, the Cochrane Vascular Information Specialist searched the Specialised Register (January 2017) and the Cochrane Central Register of Controlled Trials (CENTRAL; 2017, Issue 1). In addition, we searched trials registries (January 2017) and contacted pharmaceutical manufacturers, in our efforts to identify unpublished data and ongoing trials. Selection criteria Randomised controlled trials describing the efficacy and safety of prostanoids compared with placebo or other pharmacological control treatments for patients presenting with CLI without chance of rescue or reconstructive intervention. Data collection and analysis Two review authors independently selected trials, assessed trials for eligibility and methodological quality, and extracted data. We resolved disagreements by consensus or by consultation with a third review author. Main results For this update, 15 additional studies fulfilled selection criteria. We included in this review 33 randomised controlled trials with 4477 participants; 21 compared different prostanoids versus placebo, seven compared prostanoids versus other agents, and five conducted head-to-head comparisons using two different prostanoids. We found low-quality evidence that suggests no clear difference in the incidence of cardiovascular mortality between patients receiving prostanoids and those given placebo (risk ratio (RR) 0.81, 95% confidence interval (CI) 0.41 to 1.58).We found high-quality evidence showing that prostanoids have no effect on the incidence of total amputations when compared with placebo (RR 0.97, 95% CI 0.86 to 1.09). Adverse events were more frequent with prostanoids than with placebo (RR 2.11, 95% CI 1.79 to 2.50; moderate-quality evidence). The most commonly reported adverse events were headache, nausea, vomiting, diarrhoea, flushing, and hypotension. We found moderate-quality evidence showing that prostanoids reduced rest-pain (RR 1.30, 95% CI 1.06 to 1.59) and promoted ulcer healing (RR 1.24, 95% CI 1.04 to 1.48) when compared with placebo, although these small beneficial effects were diluted when we performed a sensitivity analysis that excluded studies at high risk of bias. Additionally, we found evidence of low to very low quality suggesting the effects of prostanoids versus other active agents or versus other prostanoids because studies conducting these comparisons were few and we judged them to be at high risk of bias. None of the included studies assessed quality of life. Authors' conclusions We found high-quality evidence showing that prostanoids have no effect on the incidence of total amputations when compared against placebo. Moderate-quality evidence showed small beneficial effects of prostanoids for rest-pain relief and ulcer healing when compared with placebo. Additionally, moderate-quality evidence showed a greater incidence of adverse effects with the use of prostanoids, and low-quality evidence suggests that prostanoids have no effect on cardiovascular mortality when compared with placebo. None of the included studies reported quality of life measurements. The balance between benefits and harms associated with use of prostanoids in patients with critical limb ischaemia with no chance of reconstructive intervention is uncertain; therefore careful assessment of therapeutic alternatives should be considered. Main reasons for downgrading the quality of evidence were high risk of attrition bias and imprecision of effect estimates.